Total suspended solids (TSS) removal from mineral processing tailings using an anionic flocculant - Isidro, Donamae B.; Mendoza, Herman D. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The research aims to remove the total suspended solids (TSS) of the mineral processing tailings from UP-DOST Field-Testing Project of Bicol Ore using an anionic flocculant to comply with the environmental standards for effluent. Removal of TSS was measured based on turbidity and was investigated as a function of polymer dosage, pH, mixing speed, and sedimentation time. Effective turbidity removal was attained at these optimized process conditions: pH of 9, flocculant dosage of 24 gpt, mixing speed of 56 rpm (G of 62 sec-1), and 25-min sedimentation time. Polymer bridging mechanism, resulting in faster settling rate, was favoured at high pH condition using the anionic flocculant, while low pH condition promoted the gradual settling by gravity of solids. Response surface model using Box-Behnken design was developed to evaluate and analyse the turbidity and to assess the interactive relationship between the process variables. The refined surface model presented that dosage and pH were the strongest drivers for turbidity removal, and interactive relationships existed between dosage-pH, and dosage-sedimentation time. General trends showed that shifting the process parameters toward these conditions increases the likelihood of obtaining acceptable turbidity values: high flocculant dosage (25 gpt), low pH (6), mean or mid-level mixing speed (60 rpm, G of 68 sec-1), and high sedimentation time (45 min)
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Flocculation; Flocculants; Tailings (Metallurgy); Turbidity; Water quality; Total suspended solids (TSS).; Response surface methodology (RSM).; Box-Behnken design